Historical Perspective dalam Standar Akuntansi Pemerintahan - Dwi Urip Wardoyo; Tommy Satrio Wicaksono; Teta Difara Anugrah Putri (CV. Ulil Albab Corp, 2022)
The practice of accounting and financial reporting is very rapid, its development is not only in Indonesia but also in other countries. Before Indonesia's independence, the management of Indonesian state finances referred to the Indische Comptabiliteitswet (ICW) created by the Dutch colonial government. Provisions in the ICW, including provisions related to accountability for government financial management, continued to be used for decades after the declaration of independence of the Indonesian state. The development of government financial accounting and reporting in Indonesia has accelerated since the implementation of state financial reform. Currently, the government sets Government Accounting Standards (SAP).